2024
DOI: 10.1021/acs.chemrev.3c00551
|View full text |Cite
|
Sign up to set email alerts
|

Do Ionic Liquids Exhibit the Required Characteristics to Dissolve, Extract, Stabilize, and Purify Proteins? Past-Present-Future Assessment

Pankaj Bharmoria,
Alesia A. Tietze,
Dibyendu Mondal
et al.

Abstract: Published as part of Chemical Reviews virtual special issue "Ionic Liquids for Diverse Applications".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 401 publications
(1,014 reference statements)
0
5
0
Order By: Relevance
“…Therefore, it is imperative to control these factors during extraction to preserve protein integrity. Buffering solutions maintain pH stability, low temperatures reduce protease activity, and additives like salts, protease inhibitors, osmolytes, and reducing agents shield proteins from environmental stressors [43]. By carefully managing these factors, successful protein extraction can yield active proteins suitable for downstream applications.…”
Section: Protein Stabilitymentioning
confidence: 99%
“…Therefore, it is imperative to control these factors during extraction to preserve protein integrity. Buffering solutions maintain pH stability, low temperatures reduce protease activity, and additives like salts, protease inhibitors, osmolytes, and reducing agents shield proteins from environmental stressors [43]. By carefully managing these factors, successful protein extraction can yield active proteins suitable for downstream applications.…”
Section: Protein Stabilitymentioning
confidence: 99%
“…Due to their specific properties, they are considered alternatives to the use of some organic or inorganic chemicals and have the possibility of being used in customization (task-specific ILs) according to special applications, which expands their usefulness to various fields of interest, such as protein dissolution, stabilization, extraction, purification, etc. [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seeking a thermodynamically favorable state, the misfolded proteins aggregate in highly organized cross-β-sheet-rich fibrillar structures stabilized by supramolecular interactions, such as hydrogen, hydrophobic, electrostatic, and van der Waals interactions . Nonetheless, if properly designed, ionic liquids (ILs) have emerged as biocompatible organic salts, exhibiting distinct effects on protein stabilization depending on protein features and the concentration and ionic components of the IL . While several studies have explored ILs as protein stabilizers, alternative approaches have demonstrated an interesting potential of these ionic compounds to act as promoters of protein fibrillation. ,, For example, at low concentrations, ILs act as adjuvants and interact with proteins in associative forms through ion-specific interactions (e.g., triple ions, contact ion pairs) with the protein surface, where IL ions displace water from the hydration layer to destabilize proteins.…”
mentioning
confidence: 99%
“…While several studies have explored ILs as protein stabilizers, alternative approaches have demonstrated an interesting potential of these ionic compounds to act as promoters of protein fibrillation. ,, For example, at low concentrations, ILs act as adjuvants and interact with proteins in associative forms through ion-specific interactions (e.g., triple ions, contact ion pairs) with the protein surface, where IL ions displace water from the hydration layer to destabilize proteins. At high concentrations, ILs act as cosolvents, where they form coclusters with the water in the hydration layer of proteins, stabilizing them via hydrophobic solvation, preferential exclusion, and hydrogen bonding . Contrary to stabilization/destabilization, protein fibrillation involves a conformational transition of protein/proteome to cross-β-type secondary structural conformation, which is driven by multiple interactions of the fibrillation agent (e.g., ionic liquid) with hydrophobic, hydrogen bonding, and ionic sites of the acid-denatured protein/proteome. , …”
mentioning
confidence: 99%
See 1 more Smart Citation